Encyclopedia of Africa - Appiah, Anthony; Gates, Henry Louis, Jr. (Oxford ; New York : Oxford University Press, 2010)
"The Encyclopedia of Africa focuses on African history and culture with articles that cover prominent individuals, events, trends, places, political movements, art forms, business and trade, religions, ethnic groups, organizations, and countries throughout Africa"--Provided by publisher.
Includes bibliographical references (v. 2, p. 587-589) and index.
Keywords: Africa -- Encyclopedias; Encyclopedias